2019
DOI: 10.3892/ol.2019.10590
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the immediate early response 5 gene increases the radiosensitivity of HeLa cells

Abstract: The effects of the immediate early response 5 ( IER5 ) gene on the sensitivity of HeLa cells to radiation remain unclear. In the present study, stably transfected HeLa cells resulting in the knockdown or overexpression of IER5 were investigated. In addition, xenografts of normal, IER5 -silenced and -overexpressed HeLa cells were injected into nude mice and examined. The results demonstrated that the radiosensitivity of the IER5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Growth-promoting stimuli and genotoxic factors such as radiation can activate IER5 expression Shi et al, 2016). IER5 may influence cell proliferation along with survival in response to ionizing radiation and thermal stress by regulating cell cycle checkpoints (Ding et al, 2009(Ding et al, , 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Growth-promoting stimuli and genotoxic factors such as radiation can activate IER5 expression Shi et al, 2016). IER5 may influence cell proliferation along with survival in response to ionizing radiation and thermal stress by regulating cell cycle checkpoints (Ding et al, 2009(Ding et al, , 2019.…”
Section: Discussionmentioning
confidence: 99%
“…In S. pombe, previous studies have found that high dNTP levels can lead to increased DNA damage sensitivity and slow progression through S-phase (Fleck et al, 2013;Pai and Kearsey, 2017). A recent study has suggested a role for PAF1 in attenuating radiosensitivity by inhibiting immediate-early response 5 (IER5) transcription, which is involved in cell cycle regulation (Ding et al, 2019;Zheng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…IER2 participates in the regulation of normal embryonic development, cell motility, senescence and death [29][30][31][32][33]. The IER5 gene is a target of HSF1 and the tumour suppressor p53, and IER5 expression is associated with proteotoxic and genotoxic stress responses as well as cell proliferation [22,23,[34][35][36].…”
Section: Introductionmentioning
confidence: 99%